2022
DOI: 10.1088/1741-2552/ac7e6c
|View full text |Cite
|
Sign up to set email alerts
|

Automated optimization of deep brain stimulation parameters for modulating neuroimaging-based targets

Abstract: Objective. Therapeutic efficacy of deep brain stimulation (DBS) in both established and emerging indications, is highly dependent on accurate lead placement and optimized clinical programming. The latter relies on clinicians’ experience to search among available sets of stimulation parameters and can be limited by the time constraints of clinical practice. Recent innovations in device technology have expanded the number of possible electrode configurations and parameter sets available to clinicians, amplifying… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…This approach involves visualization of the lead and different contacts in relation to the relevant nuclei. Studies have shown that image-guided programming can be significantly less time-consuming whilst still leading to non-inferior motor improvements compared to conventional programming ( Pourfar et al, 2015 ; Lange et al, 2021 ; Malekmohammadi et al, 2022 ). More recently, image-guided approaches also visualize the DBS-induced spread of electrical stimulation to give the programmer a clearer theoretical indication of the stimulated area, such as the electric field (EF), to guide and improve stimulation effects ( Hemm et al, 2005 ; Åström et al, 2009 ; Nguyen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This approach involves visualization of the lead and different contacts in relation to the relevant nuclei. Studies have shown that image-guided programming can be significantly less time-consuming whilst still leading to non-inferior motor improvements compared to conventional programming ( Pourfar et al, 2015 ; Lange et al, 2021 ; Malekmohammadi et al, 2022 ). More recently, image-guided approaches also visualize the DBS-induced spread of electrical stimulation to give the programmer a clearer theoretical indication of the stimulated area, such as the electric field (EF), to guide and improve stimulation effects ( Hemm et al, 2005 ; Åström et al, 2009 ; Nguyen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the utilization of optimization routines for programming SCS and other neurostimulation approaches is limited. Many optimization studies in the neurostimulation field focus on DBS [57][58][59][60] with some of them focusing on retinal prostheses [61][62][63][64][65]. These studies use analytic methods [57] or heuristic approaches [58].…”
Section: Discussionmentioning
confidence: 99%
“…Platform supporting this vision, developed in collaboration with Brainlab Inc., include commercially available GUIDE XT and STIMVIEW XT which integrate BSN’s Stimulation Field Models (SFMs) with automatic detection of lead location and orientation, and places these models in an auto-segmented, patient specific anatomy ( Lange et al, 2021 ; Waldthaler et al, 2021 ). More recent advances include the DBS Illumina 3D algorithm which is an optimization algorithm that synthesizes imaging-based information to optimize SFM size, shape, and location to accelerate Image Guided Programming ( Malekmohammadi et al, 2022 ). BSN is working to make this algorithm commercially available in the future.…”
Section: Cutting Edge Technologies From the Industry Sectormentioning
confidence: 99%